Do the more-educated prefere smaller families? - Frank Heiland; Alexia Prskawetz; Warren C. Sanderson (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2005)
This study investigates the relationship between education and desired family size in Western Europe. Using rich individual-level data from West Germany we find that more-educated men and women are more likely to prefer a family of three (or more) children over a family of two children compared to individuals with average schooling. We also find some evidence that the more-educated are less likely to favor childlessness or the one-child family over having two children. Replication of the analysis with multinational data indicates that this novel relationship holds more broadly in Western Europe. Since higher education is associated with lower realized fertility, we confirm that the gap between desired and actual fertility is largest for the more-educated. We argue that these individuals deserve more attention in the current policy debate since their fertility may be particularly responsive to interventions that help them remove the obstacles to having the family of two or more children that many of them still desire.
Keywords: 300; Fertility Preferences; Desired Family Size; Education; West Germany; Western Europe; Bildungsniveau; Familienplanung; Familie; Deutschland; Westeuropa